Business Dynamics During the Covid-19 Pandemic at Liquidity Level Basic Chemical Industry and Consumer Goods Companies in Indonesia - Hanifah, Risti Ulfi; Widyakto, Adhi; Rinawati, Tri (Universitas Semarang, 2022)
Researchers want to prove the ratio of debt as well as turnover from inventory, receivables, working capital and also company size to liquidity and its impact during the covid-19 pandemic. The research sample uses basic Chemical industry and consumer goods listed on the IDX for the fourth quarter of 2019 to the first quarter of 2020. This research is quantitative research and secondary data consisting of quarterly financial reports on the IDX. Sampling was carried out using purposive sampling method and produced 135 samples of companies. The method used is the panel data regression analysis method. The results of the analysis show that only the debt ratio has a significant negative reaction on liquidity. Company size, accounts receivable turnover, inventory turnover and working capital turnover are not significant because the increase or decrease in the variable does not affect the level of liquidity. During this covid-19 pandemic, there is no change in the relationship between each independent variable to liquidity.